1990
DOI: 10.1111/j.1476-5381.1990.tb12996.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anticholinesterases on the latencies of action potentials in mouse skeletal muscles

Abstract: 1 The purpose of this investigation was to determine the long-term effects of a single dose of persistent anticholinesterases on muscle action potentials evoked by nerve stimulation. 2 Action potentials (APs), elicited by stimulation of the phrenic nerve, were recorded intracellularly in muscle fibres of mouse diaphragm. The time between stimulus and AP was measured and the variability of this latency was calculated during trains of APs. At the beginning of trains of APs there was an increase in latency, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The acetylcholinesterase activity of diaphragm homogenates was inhibited rapidly after the injection of ECO and its recovery was evident 1 day later (Townsend, 1988;Bamforth, 1989) and was complete by 5 days (Kelly et al, 1990 (Dirnhuber & Green, 1978;French et al, 1979;Leadbeater et al, 1985). In our experiments, protection by PYR of some of the AChE against inhibition of ECO or the early reactivation of some of the ECO-inhibited enzyme with 2PAM, was associated with prevention of increased MCD or delay.…”
Section: Discussion Effects Ofprotecting or Reactivating Acetylcholinmentioning
confidence: 57%
See 3 more Smart Citations
“…The acetylcholinesterase activity of diaphragm homogenates was inhibited rapidly after the injection of ECO and its recovery was evident 1 day later (Townsend, 1988;Bamforth, 1989) and was complete by 5 days (Kelly et al, 1990 (Dirnhuber & Green, 1978;French et al, 1979;Leadbeater et al, 1985). In our experiments, protection by PYR of some of the AChE against inhibition of ECO or the early reactivation of some of the ECO-inhibited enzyme with 2PAM, was associated with prevention of increased MCD or delay.…”
Section: Discussion Effects Ofprotecting or Reactivating Acetylcholinmentioning
confidence: 57%
“…Considering these results in isolation, it might seem that initiation of increased jitter requires inhibition of more than 75% of the AChE. However, Kelly et al (1990) showed that ECO 0.3 mol kg-' caused 87% inhibition at 3 h, but only an increase in delay at 5 days, and 1 mol kg-' BOS increased MCD but caused only 37% inhibition of acetylcholinesterase. Thus there appears to be no simple relationship between increased jitter and the maximum inhibition of the AChE of diaphragm homogenates at 3 h after injection of organophosphate.…”
Section: Discussion Effects Ofprotecting or Reactivating Acetylcholinmentioning
confidence: 96%
See 2 more Smart Citations
“…Experiments reported by Kelly et al (1990) showed that the 'jitter' i.e. the variability of latencies of indirectly-elicited diaphragm muscle action potentials was increased 5 days after administration of a single dose (0.5 jmol kg-') of ecothiopate, a quaternary organophosphate.…”
Section: Introductionmentioning
confidence: 99%